2019
DOI: 10.12775/eq.2020.001
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the discovery and ecology of the invasive armoured catfish Pterygoplichthys disjunctivus (Weber, 1991) and the exotic cichlid Amphilophus trimaculatus (Gunther, 1867) from Southern West Bengal, India

Abstract: This paper documents the first occurrence of an intergrade form of the highly invasive, South American armoured suckermouth catfish Pterygoplichthys disjunctivus (Weber, 1991) from the brackish waters of the Sundarban Tiger Reserve, West Bengal, India and the exotic Central American cichlid Amphilophus trimaculatus (Gunther, 1867) from Southern Bengal, India. Another species of cichlid Etroplus suratensis (Bloch, 1790) native to Southern India is also recorded for the wild for the first time from West Bengal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The present study confirmed the presence of A. trimaculatus in the River Cauvery basin indicating the non-native range extension of the species in India (Chakraborty et al, 2019;Knight & Devi, 2009). et al, 2008), and the largest Cauvery female A. trimaculatus (20.1 cm TL) approached the reported female maximum of 25.0 cm TL (Corfiled et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The present study confirmed the presence of A. trimaculatus in the River Cauvery basin indicating the non-native range extension of the species in India (Chakraborty et al, 2019;Knight & Devi, 2009). et al, 2008), and the largest Cauvery female A. trimaculatus (20.1 cm TL) approached the reported female maximum of 25.0 cm TL (Corfiled et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…et al, 2008), and the largest Cauvery female A. trimaculatus (20.1 cm TL) approached the reported female maximum of 25.0 cm TL (Corfiled et al, 2008). The sizes of A. trimaculatus reported from the earlier records in India ranged from 3.5 to 16.5 cm (Chakraborty et al, 2019;Knight & Devi, 2009), indicating that the specimens in the present study have maximum TL as recorded from natural waters in India. Amphilophus trimaculatus is a euryphagous fish that feeds on small fishes, aquatic macro-invertebrates and both aquatic and terrestrial insects (Corfield et al, 2008).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We measured the impact of catfish over both structural (growth of co-occurring species) and functional components (nutrient dynamics in the form of chlorophyll 'a', soil nutrients as well as hydrological parameters) of the mesocosm ponds. Several species of the catfish have invaded peninsular India, and most species hybridize a lot (Jumawan et al, 2011;Chakraborty et al, 2020). Thus, in this paper, we refer to sailfin catfish by including any species that belongs to the Pterygoplichthys genus.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a number of introduced non-native ornamental fish are plying in aquarium trade and pet keeping (Singh et al, 2013b;Sandiliyan, 2016). As a result, several introduced non-native species of aquaculture and aquarium are now available in open waters including the forest reserves, protected areas and even coastal areas Lakra, 2011, Singh et al, 2013a;Sandilyan, 2016;Raj et al, 2019;Chakraborty et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%